Challenges facing primary and tertiary language teachers in implementing CALL - Mat Daud, Nor Shidrah; Mat Daud, Nuraihan (IIUM Press, 2012)
Language teachers at all levels are being encouraged to integrate technology into teaching. Yet each has his/her own story to tell where implementation is concerned. This paper attempts to capture the experience of teachers in two different settings with regard to technology integration in language teaching. It focuses on language teachers teaching in primary and tertiary institutions. A survey was conducted to investigate if they are equally prepared for the integration and whether they share the same interest in technology. The extent to which the teachers are using computers in teaching will also be presented. The obstacles to the adoption of technology in their language classrooms will also be discussed. The subjects of the study were lecturers of the Academy of Language Studies UiTM Terengganu (a public university in the East Coast of Malaysia) and primary school teachers in a number of states in Malaysia.